Thermodynamic and NMR Assessment of Ligand Cooperativity and Intersubunit Communication in Symmetric Dimers: Application to Thymidylate Synthase - Lee, Andrew L.; Sapienza, Paul J. (Frontiers in Molecular Biosciences, 2018)
Thymidylate synthase (TS) is a homodimeric enzyme with evidence for negative regulation of one protomer while the other protomer acts on substrate, so called half-the-sites reactivity. The mechanisms by which multisubunit allosteric proteins communicate between protomers is not well understood, and the simplicity of dimeric systems has advantages for observing conformational and dynamic processes that functionally connect distance-separated active sites. This review considers progress in overcoming the inherent challenges of accurate thermodynamic and atomic-resolution characterization of interprotomer communication mechanisms in symmetric protein dimers, with TS used as an example. Isothermal titration calorimetry is used to measure ligand binding cooperativity, even in cases where the two binding enthalpies are similar, and NMR spectroscopy is used to detect site-specific changes occurring in the two protomers. The NMR approach makes use of mixed-labeled dimers, enabling protomer-specific detection of signals in the singly ligated state. The rich informational content of the NMR signals from the singly ligated state, relative to the apo and saturated states, requires new considerations that do not arise in simple cases of 1:1 protein-ligand interactions.